Situation of Artificial Intelligence in Ecuador in relation to the leading countries of the Southern Cone region - Barragán-Martínez, Xavier (2023)
The objective of this work is to identify and understand the status of the Artificial Intelligence (AI) ecosystem in Ecuador, for which a methodology for measuring the status of AI applied to the leading countries in this area of the region is defined, pretending to reflect the situation of the Artificial Intelligence Ecosystem; therefore, the Tortoise AI Index methodology is taken as a reference, which defines three pillars of analysis; investment, innovation and implementation, which uses 143 indicators divided into seven sub-pillars: Talent, Infrastructure, Operating Environment, Research, Development, Government and Commercial Strategy. The proposal maintains the first five subpillars and uses a new one called Institutionality that integrates government and commercial strategies. The research subscribes to a descriptive, quantitative and analytical method of reviewing secondary sources and databases of organizations, companies, governments, among others. The findings show that there is a significant gap when comparing the AI ecosystem in Ecuador with the ecosystems of Argentina, Brazil, Chile, Colombia, and Uruguay; showing an incipient use, adoption of this technology and the lack of public policies that encourage the use of AI as a means of social, economic and environmental development.